Effect of bulb size on seed yield of onion (Allium cepa L.) - Ripon, Md.; Mahmud, Riad; Nayem, Jannatul; Monika, Fahmida Sultana; Mohsin, Gazi Md. (Journal of Plant Stress Physiology, 2025)
The purpose of this study was to determine the bulb size on seed yield of onion (Allium cepa L.). The experiment was carried out over four months at Noakhali Science and Technology University. Normal environmental condition bulbs of different sizes were accordingly chosen and sown. Some minor factors, for instance, seed yield, thousands seed weight and germination rate were set and noted. Many times, the facts that were established were the line with our expectation of the link between bulb size and seed yield. Field grown bulbs producing larger flowers (40 g) always recorded higher seed yields as compared to the small bulbs (20 g). Additionally, bigger bulbs (40 g) specified even better germination incidences, hence showing a relationship between bulb size and seed quality. Based on these results, it might be postulated that in onion seed production appropriate classification of bulbs to produce seeds should be taken into consideration to obtain high quality seeds. Further studies can advance the understanding of a better way of cultivating to increase the efficiency of onion seed production.